2023
DOI: 10.1101/2023.10.05.560930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting LC3/GABARAP for degrader development and autophagy modulation

Martin P. Schwalm,
Johannes Dopfer,
Adarsh Kumar
et al.

Abstract: Recent successes in developing small-molecule degraders that act through the ubiquitin system have spurred efforts to extend this technology to other mechanisms, including the autophagosomal-lysosomal pathway. Therefore, reports of autophagosome tethering compounds (ATTECs) have received considerable attention from the drug development community. ATTECs are based on the target recruitment to LC3/GABARAP, a family of membrane-bound proteins that tether autophagy receptors to the autophagosome. In order to valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…They found that 1 binds weakly to GABARAP-L2 and has weak, if any, binding to LC3B. 32 In that work, the authors suggested that these activities were too weak to account for the compound’s ability to mediate targeted degradation.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…They found that 1 binds weakly to GABARAP-L2 and has weak, if any, binding to LC3B. 32 In that work, the authors suggested that these activities were too weak to account for the compound’s ability to mediate targeted degradation.…”
Section: Figurementioning
confidence: 99%
“…The similarity of compound 1-induced CSP patterns observed for GABARAPL2 (ref. 32) and GABARAP (this study) attests to the high conservation of the core LIR docking site and to the challenges of devising small-molecule ligands targeting individual family members. More broadly, this work adds to the growing evidence that these protein-protein interactions are highly likely to be druggable using orally bioavailable small molecules.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The recent research suggests that compound 1 may not interact with LC3 . To further verify the direct interaction between compound 12c and LC3 protein, MicroScale Thermophoresis (MST) method was used to assess the binding affinity of compound 12c toward LC3.…”
mentioning
confidence: 99%
“…The recent research suggests that compound 1 may not interact with LC3. 29 To further verify the direct interaction between compound 12c and LC3 protein, MicroScale Thermophoresis (MST) method was used to assess the binding affinity of compound 12c toward LC3. The determined K D value of 187 nM demonstrated the potent and effective binding capability of compound 12c with LC3 (Figure S3 in the Supporting Information).…”
mentioning
confidence: 99%